2001
DOI: 10.1068/p3008
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Presentation Format and Viewer Training in the Visual Arts on the Perception of Pictorial and Aesthetic Qualities of Paintings

Abstract: The comparability of viewers' responses to slide-projected and computer-generated images of nine paintings by renowned artists to those obtained from individuals experiencing the originals in the galleries of the New York Metropolitan Museum of Art was investigated. The influence of training in the visual arts upon evaluative judgments made under the three presentation formats was also assessed. Specifically, art-trained and untrained participants in each format condition rated each artwork on sixteen measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
159
6
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(185 citation statements)
references
References 5 publications
18
159
6
2
Order By: Relevance
“…Fluid intelligence and the creativity of people's college majors had little to do with aesthetic chills scores; gender primarily predicted feeling touched rather than chills. A large literature shows that expertise moderates many aesthetic processes, such as how people perceive, understand, evaluate, and experience art ( Hekkert & van Wieringen, 1996a, Hekkert & van Wieringen, 1996bLocher, Smith, & Smith, 2001;Parsons, 1987;Silvia, 2006;Silvia & Berg, in press). People with more expertise in the arts reported feeling aesthetic chills more often, but it remains for future work to discern why.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid intelligence and the creativity of people's college majors had little to do with aesthetic chills scores; gender primarily predicted feeling touched rather than chills. A large literature shows that expertise moderates many aesthetic processes, such as how people perceive, understand, evaluate, and experience art ( Hekkert & van Wieringen, 1996a, Hekkert & van Wieringen, 1996bLocher, Smith, & Smith, 2001;Parsons, 1987;Silvia, 2006;Silvia & Berg, in press). People with more expertise in the arts reported feeling aesthetic chills more often, but it remains for future work to discern why.…”
Section: Discussionmentioning
confidence: 99%
“…The physical artefacts were taken out of the museum setting to ensure that each modality of artefacts would be shown in the same space so participants can evaluate them under consistent conditions. In addition, since past studies have indicated that the museum environment influences emotions (Locher et al 2001;Taylor 2001), showing all the modalities, including the physical modality, outside of the museum can further demonstrate the potential for the artefacts to influence emotional connections.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Previous studies have claimed that emotional responses to artworks and objects in museums are influenced by a museum's environment and seeing original objects (Gadsby 2011;Locher et al 2001;Taylor 2001). In addition, these emotional responses are considered the most important part of understanding museum objects (Taylor 2009).…”
Section: Emotional Responsesmentioning
confidence: 99%
See 2 more Smart Citations